Partitioning of heavy metals in the particulate and gaseous emission, clinker and ESP dust in cement kiln at steady state condition - Margarito, Marianito T. (2006)
Test runs using industrial waste materials as alternative fuel and material substitute in cement manufacturing are now being done in the Philippines. EMB-DENR is in the process of promulgating policies that would regulate co-processing of wastes in cement kiln so as not to compromise human health, safety and environment. Some of the waste materials being co-processed in cement kilns contain organic and heavy metals. Heavy metals are of concern since these are not degraded or destroyed in the process.
This study was undertaken to investigates the fate of heavy metals introduced with wastes, raw materials and fuel in the cement kiln utilizing results of test runs conducted in a cement manufacturing plants. This study determined the influence of operating parameters and other factors on the behavior of heavy metals in the cement kiln. Particular attention was given to the distribution of these metals in the output streams and the influence of operating temperature, chlorine input and the source of heavy metals. The results of test runs conducted were also used to determine emission factors for heavy metals including their dependence on operating temperature. Results showed that relative volatility is an important factor in the behavior of metals and that the distribution of certain heavy metals in the output streams was insensitive to operating parameters. Actual emissions were compared with calculated emissions using Enrichment Factor of the Electrostatic Precipitator (ESP) dust and Emission Factor (EF) with and without temperature correction. Comparison showed that better prediction is achieved using Emission Factor with temperature correction.
"May 2006."
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Cement -- Analysis; Cement kilns; Heavy metals -- Analysis; Sewage -- Purification -- Heavy metals removal -- Philippines; Cement plants -- Philippines